Toward A Contemplative Technopedagogy Framework: A Discourse Analysis - Shanks, Justin D. (Frontiers in Education, 2020)
Digital technology features prominently in the higher education ecosystem, affecting the ways in which educators think, communicate, and teach. This research applies discourse analysis to articles published within The Chronicle of Higher Education (CHE) to understand: (1) The ways in which conceptions of digital technology in higher education pedagogy have changed and the ways in which they have remained consistent from 1993-2016 and (2) The extent to which CHE articles addressed attributes of contemplation with regard to technopedagogy. Research findings indicate that during the previous 23 years digital technology was portrayed as an overwhelmingly positive addition to higher education pedagogy. Less than half of articles analyzed contained attributes of contemplation. Non-contemplative technopedagogical approaches can lead to uncritical adoption or knee-jerk dismissal of digital technology – either of which can have substantial and long-lasting consequences within teaching-learning environments. Contemporary pedagogies need to pay closer attention to digital technologies, but must do so in a purposeful and engaged manner. This historical and discursive research inductively led to the development of the Contemplative Technopedagogy Framework, which provides an approachable introduction to using attributes of contemplation when making pedagogical decisions about digital technology in higher education.